Predictive value of ophthalmic artery doppler in pre-eclampsia development - Adlakha, Eena; Khanijo, Vandana; Unni, Jyothi; Bapat, Anita; Thakar, Saket (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Objective: To evaluate the predictive value of maternal ophthalmic artery Doppler parameters, both independently and in combination with uterine artery pulsatility index (UtA-PI) and mean arterial pressure (MAP), in forecasting pre-eclampsia (PE) development. Methods: This prospective observational study involved women at 19-23 weeks’ gestation. Maternal demographics, medical history, ultrasound for fetal anatomy and growth, and Doppler measurements of ophthalmic artery flow velocities (PSV1, PSV2, PSV ratio) along with MAP and UtA-PI were assessed. Results: The incidence of PE was 9.4%. Women with PE were older (35.8 vs. 32.3 years, p<0.01). Seventy-five percent developed early-onset PE. Mean UtA-PI was higher in PE cases (1.91 vs 1.27, p=0.03). UtA-PI showed good predictive value with 83.3% sensitivity and 68.7% specificity (accuracy: 76%). Ophthalmic artery parameters, particularly PSV2 (27.54 vs. 23.46, p<0.01) and PSV ratio (0.8 vs. 0.61, p<0.01), were significantly higher in PE cases. These parameters had sensitivity and specificity of 83.3%/58.3% (PSV2) and 83.3%/61.7% (PSV ratio), respectively. Combined ophthalmic artery Doppler parameters showed strong predictive value (AUC 0.832), with sensitivity 58.3%, specificity 90.4%, and accuracy 87.4%. Adding uterine and ophthalmic artery Doppler parameters increased accuracy to 91.3%. The combination of MAP, UtA-PI, and ophthalmic Doppler showed the highest accuracy (97.6%, AUC 0.969) with sensitivity 91.7% and specificity 98.3%. Conclusion: Ophthalmic artery PSV ratio is a promising predictor for PE development, warranting further validation in larger studies.